Analisis Peran Komunikasi Interpersonal dalam Meningkatkan Kinerja Pegawai di Kelurahan Sukosari, Kecamatan Kartoharjo Kota Madiun - Guntur Gumelar; Zuli Nurchayati; Veny Ari Sejati (SENTRI: Jurnal Riset Ilmiah, 2026)
Communication and human resources in an organization cannot be separated, as employees carry out their duties through continuous interaction with others. Interpersonal communication is an essential form of organizational communication that positively influences relationships between superiors and subordinates and contributes to changes in attitudes and the development of more constructive working relationships. This study aims to examine the role of interpersonal communication among employees at the Sukosari Village Office, Madiun City, and to analyze its contribution to improving employee performance. This research employed a qualitative approach, producing descriptive data in the form of words. The research subjects were employees of the Sukosari Village Office, Kartoharjo District, Madiun City, with data collected through interviews, observation, and documentation. The findings indicate that the four indicators of interpersonal communication openness, supportiveness, positivity, and equality have been implemented at an adequate level and function synergistically. Nevertheless, several obstacles were identified, including technical constraints such as limited communication facilities and psychological barriers such as reluctance to express opinions and differences in individual attitudes. These barriers are addressed through effective interpersonal communication, particularly openness and supportiveness, which facilitate mutual understanding, reduce miscommunication, and strengthen trust among employees. Employee performance, measured through quality, quantity, responsibility, cooperation, and initiative, is categorized as good, reflecting commitment, teamwork, and initiative that support sustainable organizational performance improvement.